2017
DOI: 10.3945/ajcn.116.150136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary sodium on metabolites: the Dietary Approaches to Stop Hypertension (DASH)–Sodium Feeding Study

Abstract: Background: High sodium intake is known to increase blood pressure and is difficult to measure in epidemiologic studies. Objective: We examined the effect of sodium intake on metabolites within the DASH (Dietary Approaches to Stop Hypertension Trial)-Sodium Trial to further our understanding of the biological effects of sodium intake beyond blood pressure. Design: The DASH-Sodium Trial randomly assigned individuals to either the DASH diet (low in fat and high in protein, low-fat dairy, and fruits and vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 39 publications
2
43
0
3
Order By: Relevance
“…However, the effects of salt intake on gut microbiota have been investigated only in very recent times. In the Dietary Approaches to Stop Hypertension (DASH)-Sodium Feeding Study, Derkach and colleagues showed that in 119 patients at high risk for hypertension, different levels of salt intake were associated with different urinary levels of several metabolites, including some of gut microbial origin [65]. Namely, high-salt intake was associated with decreased urinary levels of compounds related to fatty acid, benzoate, indole, isovalerate, methionine, and tryptophan metabolism and of the microbial metabolites 4-ethylphenylsulfate and 4-hydroxyphenylpiruvate [65].…”
Section: Salt and Microbiotamentioning
confidence: 99%
“…However, the effects of salt intake on gut microbiota have been investigated only in very recent times. In the Dietary Approaches to Stop Hypertension (DASH)-Sodium Feeding Study, Derkach and colleagues showed that in 119 patients at high risk for hypertension, different levels of salt intake were associated with different urinary levels of several metabolites, including some of gut microbial origin [65]. Namely, high-salt intake was associated with decreased urinary levels of compounds related to fatty acid, benzoate, indole, isovalerate, methionine, and tryptophan metabolism and of the microbial metabolites 4-ethylphenylsulfate and 4-hydroxyphenylpiruvate [65].…”
Section: Salt and Microbiotamentioning
confidence: 99%
“…The response of blood pressure regulation to dietary interventions has been investigated through metabolic phenotyping approaches in several studies, where different dietary patterns were adopted including the DASH Diet [ 50 52 ], Optimal Macronutrient Intake Trial for Heart Health (OmniHeart) Diets [ 56 ••], and Mediterranean Diet [ 61 ].…”
Section: Metabolic Phenotyping Dietary Intervention Studies and Blomentioning
confidence: 99%
“…The mechanisms by which low sodium loading results in a disturbed acylcarnitine profile have not been explored. Derkach et al also found a phenomenon in a DASH-sodium trial among participants with high blood pressure, that plasma metabolites of acylcarnitines (butyrylcarnitine and valerylcarnitine) were increased with sodium reduction (14). On the other hand, some studies showed a significant increase in renin-angiotensinaldosterone system activity with low sodium intake (12).…”
Section: Discussionmentioning
confidence: 97%
“…As a result, supplementation of fluid and sodium is a rationally efficient method to treat VVS (13). A possible relationship between the metabolism of carnitine and acylcarnitines and the reducing intake of sodium was mentioned among adults with hypertension (14). However, it is unclear whether low sodium intake in patients with VVS leads to abnormal changes in carnitine and acylcarnitines, which mediates the occurrence of syncope.…”
Section: Introductionmentioning
confidence: 99%